Persepsi Positif Generasi Z Terhadap Teknologi Perbankan (Studi Kasus pada Mahasiswa UIN KH ABDURRAHMAN WAHID Pekalongan) - Aghuts Naufal R; Safinatul Iza; Mustofiatul Aini; Selisa Nur Leoni; Fika Qonita (Global Leadership Organizational Research in Management, 2023)
Advances in banking technology are currently very rapid, such as the emergence of digital payment methods. This digital method is enough to help humans,especially in terms of the economy, such as making transactions easier. The methodused in this research is descriptive qualitative analysis. The data collection technique in this study was by interviewing the issues discussed. This research discusses the perspective of generation Z on banking technology. The existence of banking technology certainly helps the efficiency of its users, because it can make it easier for users. Users of banking technology can certainly use it at any time without worrying about the privacy of personal data, because the service system is good and also maintains an image.